RELIGIOSITY AS PILLARS OF HOUSEHOLD INTEGRITY - Safithri, Awaliya; Ash Shiddiqi, Hasbi (Religi: Jurnal Studi Agama-agama, 2025)
This article aims to analyze the Family Resilience Bill (RUU KK) through the maqasid al-syariah approach, focusing on the three main pillars in building a harmonious household, namely love (mahabbah), religiosity (taqwa), and humanity (karāmah insāniyyah). This research uses a normative-qualitative method with a content analysis approach to the text of the KK Bill, supporting academic documents, and sources of classical and contemporary Islamic literature. The analysis is carried out by interpreting the provisions in the Bill in accordance with the five main principles of maqasid al-shariah: hifz al-din, hifz al-nafs, hifz al-'aql, hifz al-nasl, and hifz al-mal. The results of the study show that although the KK Bill has the initial spirit to strengthen the family institution, many of the provisions in it are not in line with the principles of maqasid. The rigid and normative division of roles between husband and wife still strengthens the patriarchal structure and ignores the dynamics of reciprocal relations in the household. The protection of women and children does not fully reflect distributive justice, and the value of love as a spiritual basis in the family has little space. In addition, the legalistic-repressive approach in several articles has the potential to ignore the rehabilitative and affectionate aspects as the main characteristics of maqasid in the context of Islamic family law. This research is important as an academic contribution to the development of family regulations that are more humane, inclusive, and in accordance with substantive Islamic values. Thus, future family legislation is expected to be able to bring love-based justice, liberating religiosity, and respect for the dignity of all family members. Keywords: Maqasid al-Shariah, Family Resilience, Love, Religiosity, Humanity. Artikel ini bertujuan untuk menganalisis Rancangan Undang-Undang Ketahanan Keluarga (RUU KK) melalui pendekatan maqasid al-syariah, dengan fokus pada tiga pilar utama dalam membangun rumah tangga yang harmonis, yaitu cinta kasih (mahabbah), religiusitas (taqwa), dan kemanusiaan (karāmah insāniyyah). Penelitian ini menggunakan metode normatif-kualitatif dengan pendekatan analisis isi terhadap teks RUU KK, dokumen akademik pendukung, dan sumber literatur Islam klasik dan kontemporer. Analisis dilakukan dengan menafsirkan ketentuan-ketentuan dalam RUU tersebut sesuai dengan lima prinsip utama maqasid al-syariah: hifz al-din, hifz al-nafs, hifz al-'aql, hifz al-nasl, dan hifz al-mal. Hasil penelitian menunjukkan bahwa meskipun RUU KK memiliki semangat awal untuk memperkuat institusi keluarga, banyak ketentuan di dalamnya yang tidak sejalan dengan prinsip-prinsip maqasid. Pembagian peran yang kaku dan normatif antara suami dan istri masih memperkuat struktur patriarki dan mengabaikan dinamika hubungan timbal balik dalam rumah tangga. Perlindungan terhadap perempuan dan anak belum sepenuhnya mencerminkan keadilan distributif, dan nilai kasih sayang sebagai landasan spiritual dalam keluarga kurang mendapat tempat. Selain itu, pendekatan legalistik-represif dalam beberapa pasal berpotensi mengabaikan aspek rehabilitatif dan afeksi sebagai ciri utama maqasid dalam konteks hukum keluarga Islam. Penelitian ini penting sebagai kontribusi akademis bagi pengembangan regulasi keluarga yang lebih humanis, inklusif, dan sesuai dengan nilai-nilai Islam yang substantif. Dengan demikian, legislasi keluarga ke depan diharapkan mampu menghadirkan keadilan berbasis kasih sayang, religiusitas yang memerdekakan, dan penghormatan terhadap martabat seluruh anggota keluarga. Kata Kunci: Maqasid al-Syariah, Ketahanan Keluarga, Kasih Sayang, Religiusitas, Kemanusiaan.